2008
DOI: 10.2174/138620708783744462
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Aptamer Libraries

Abstract: Peptide aptamers are molecules that bind to protein targets and are able to interfere with their functions. In the past, important achievements have been made using such peptide aptamers in different approaches and for various purposes. Peptide aptamers are comprised of a variable peptide region of 8 to 20 amino acids in length, which is displayed by a scaffold protein. An overview of the numerous scaffold proteins that have been investigated for their suitability to present peptide aptamers will be given. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…The scaffold has to be soluble, non-toxic and capable of high-level expression in prokaryotic systems. The cloned scaffold gene should be engineered to accommodate functional protein elements such as localization signals, and epitope and purification tags [57]. It is highly desirable that permutations introduced into variable regions do not adversely affect solubility, folding and the aggregating properties of the resulting combinatorial product.…”
Section: Scaffoldsmentioning
confidence: 99%
See 2 more Smart Citations
“…The scaffold has to be soluble, non-toxic and capable of high-level expression in prokaryotic systems. The cloned scaffold gene should be engineered to accommodate functional protein elements such as localization signals, and epitope and purification tags [57]. It is highly desirable that permutations introduced into variable regions do not adversely affect solubility, folding and the aggregating properties of the resulting combinatorial product.…”
Section: Scaffoldsmentioning
confidence: 99%
“…Employing the yeast two-hybrid method a number of peptide aptamers, such as PA against human cyclin-dependent kinase 2 (Cdk2) [37] and E2F transcription factor, were identified from corresponding random loop libraries, as well as several other targets, mostly inhibitors of signaling pathways involved in cancer development and progression. Owing to its remarkable characteristics, TrxA was the first widely used peptide aptamer scaffold (see Table 1 in review [57]). In 2012 Groner et al [67] described a PA against Stat3 and Survivin, selected using human Thioredoxin (hTrx) that was modified to provide high levels of expression and facilitate cellular delivery; in 2013 the same group developed a PA against Stat5 [68].…”
Section: Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peptide aptamers are short peptides, usually 12 to 20 amino acids in length, which can be selected from random, high-complexity peptide libraries in yeast two-hybrid screens 11,35 Our experiments have shown that a variant of the human thioredoxin (hTrx), devoid of cysteine residues, provides a favorable scaffold for the display of such target interacting peptides. Appropriately appended scaffolds allow the presentation of the peptide in a constrained conformation, the production as recombinant proteins and the cellular delivery of specific peptide aptamers.…”
Section: Inhibition Of Stat3 and Survivin Through Peptide Ligandsmentioning
confidence: 99%
“…35 If the inhibition of the target protein triggers a particular phenotype, these peptide sequences can be validated as functional inhibitors upon expression in cells 39 or upon transduction of recombinant proteins into cells. 13 These cell culture experiments, however, cannot easily be extrapolated to the in vivo situation.…”
Section: Discovery Of Low Molecular Weight Inhibitors Of Peptide Protmentioning
confidence: 99%